Luqatah (Found Items) In Fiqih Muamalah - Dhini Dwi Apriyani; Salsa Nurhilda; Muhammad Nur Iqbal (Jurnal Multidisiplin Sahombu, 2025)
Luqathah is an item found in a place that does not belong to an individual. For example: a Muslim finds money or clothes on the street , because he is worried that the money or clothes will be wasted, so he takes it. Found items must be announced for at least one year. For example, when the person who finds it has announced it for one year or more, the finder has not found the owner of the item, then the item may be used. The data collection used in this journal uses the library study method . By referring to primary sources such as hadith books and other secondary sources that contain and relate to the problem discussed,. Results The similarities and differences between luqathah (found items) in Islamic law and civil law are, an item that is lost from its owner and then found and taken by someone else. The items are general in nature such as money, gold, electronic goods, food, lost (stray) animals, and others. The law on taking found items can change depending on the conditions of the place and the ability of the finder. The loss of an item from its owner does not result in the loss of ownership of the item. The community is responsible for caring for, storing and delivering the item to its owner as best they can .